GOVERNMENT-MEDIA RELATIONS IN CANADA’S FEDERAL CYBER SECURITY (JULY - DECEMBER 2018 & 2021) - Lopez, Victoria (Université d'Ottawa | University of Ottawa, 2022)
The world is increasingly technologically connected, and those technologies are advancing at rapid pace, meaning that cyber security can seem like whack-a-mole. Malicious cyber activity plays heavily in geopolitics and governments worldwide are faced with challenges to protect their citizens and sovereignty. This research evaluates the Government of Canada’s approach to communicating with the public about cyber security activities and programming based on representations in traditional news media. It develops a model of government-media relations in federal cyber security activities and programming based on cross-sectional analysis of two six-month periods (from July – December in 2018 and 2021). These periods correspond to the six months following the release of Canada’s most recent highest-level strategy for cyber security, the National Cyber Security Strategy, and a contemporary period. It assesses the representations and analyzes some relevant themes throughout like the Huawei 5G story that spans the timeframe. This is largely an assessment of what gets picked up in traditional news media and contextually why that is. There appeared to be a predominantly information dissemination model of government-media relations which neither favoured or dissented the Government of Canada’s activities and programming in cyber security. There was some evidence of a two-way asymmetric model, but this could not be determined within the scope of this analysis in evaluating traditional news media content.